Time Course of CD64, a Leukocyte Activation Marker, During Cardiopulmonary Bypass Surgery. Issue 2 (February 2017) - Djebara, Sarah; Biston, Patrick; Fossé, Emmanuel; Daper, Anne; Joris, Marc; Boudjeltia, Karim Zouaoui; Lelubre, Christophe; Cauchie, Philippe; Piagnerelli, Michael
Abstract : ABSTRACT: Distinction between inflammation secondary to surgery, especially coronary artery bypass graft with cardiopulmonary bypass (CPB), and inflammation due to infection is difficult in surgical intensive care unit (ICU) patients. Development of biomarkers of infection could help clinicians in the early identification and thus treatment of sepsis in these patients. We compared the time course of the neutrophil CD64 index, a high affinity immunoglobulin FC γ receptor I whose expression is increased in bacterial infection, in 39 patients undergoing cardiac surgery with CPB and 11 patients admitted to the ICU with severe sepsis or septic shock. The CD64 index was significantly more elevated in septic patients than in patients who had CPB except at day 5. The CD64 index increased moderately on day 1 after cardiac surgery but the value remained lower than in septic patients. The duration for which the CD64 index was greater than 1.0 was longer in septic than in CPB patients. Receiver operating curves to differentiate CPB from sepsis on day 1 were not significantly different between C-reactive protein (CRP) concentrations and CD 64 index. Nevertheless, combination of low CD64 index with low CRP concentrations on day 1 ruled out sepsis except in three patients. There were no correlations between the CD64 index and cytokine levels (tumor necrosis factor [TNF]-α, interferon [IFN]γ, interleukin [IL]-6, IL-10, IL-8, IL-12) measured in subpopulations. In conclusion, CD64 index only in combination with CRP concentrations could be used to discriminate inflammation due to surgery from that due to infection in this particular population.